Towards a new generation of seasonal forecasting systems - Arribas, Alberto; Glover, Matthew; Maidens, Anna; Peterson, Kenneth Andrew; Gordon, Margaret; MacLachlan, Craig (Física de la Tierra, 2010)
Seasonal forecasting systems – and their extension to decadal timescales – are crucial in the development of adaptation strategies to climate change. However, despite important achievements in this area, significant levels of skill are only generally found over regions strongly connected with the El Nino-Southern Oscillation. With the aim of improving the skill of regional climate predictions at seasonal and decadal timescales, a new Met Office seasonal forecasting system (GloSea4) has been developed. The new system has been designed to be a flexible and easy-to-upgrade system, fully integrated within the Met Office model development infrastructure. Preliminary results from GloSea4 are positive, showing a significant increase in the skill of the forecasts over the El Niño regions.